Umm Qays, Jordan. iDAI.tutorials on the Road: a Universally Applicable Package of Teaching Materials for Finds Processing in a Field Test. Report on the Summer School 2023 - Hamel, Hanna; Möller, Heike (e-Forschungsberichte des DAI, 2023)
Due to the COVID-19-pandemic, the Summer School »Pottery Processing. Introduction to the Scientific Treatment of Ancient Ceramics« at the Museum in Umm Qays planned for 2020 had to be cancelled and was finally carried out this year (04.–12.06.2023). In the meantime, two educational videos for drawing and photographing ceramic sherds were created and tested for their »field suitability«. A complementary third part on the processing of pottery from excavation to storage in the depot was filmed during the summer school. In addition, a handout was created from the online tutorial titled »Instructions for the archaeological drawing of ceramic sherds« and made available to the students. The resulting package, which is accessible in Arabic, is intended to give students a lasting opportunity to use their acquired knowledge and to continue their education independently.